PENGARUH BROKOLI (Brassica oleracea var. Italica) DALAM MENGHAMBAT OKSIDASI LEMAK PADA NUGGET TEMPE KEDELAI SELAMA PENYIMPANAN - Emeline, Ezra A.; Taroreh, Mercy I. R.; Tuju, Thelma D. J. (Fakultas Pertanian, Universitas Sam Ratulangi, 2020)
ABSTRACTThe purpose of this research is to determine the influence of broccoli comparison in inhibiting fat oxidation of soybean tempe nugget before and after 30 days of storage and to evaluate the acceptance rate of soybean tempe nugget with broccoli comparison before and after of 30 days storage. This study consisted of 4 comparative treatments of broccoli and soybean tempe, which is 0% broccoli and 100% tempe in treatment A, 10% broccoli and 90% tempe in treatment B, 20% broccoli and 80% tempe in treatment C, and 30% broccoli and 70% tempe in the treatment D. Soybean tempe nugget is tested on 0 days and 30 days storage. The results showed the influence of the broccoli comparison in inhibiting the oxidation of tempe nuggets. Tempe nuggets with broccoli comparison is best reviewed from the levels of free fatty acids (ALB), peroxide value, and the value of thiobarbituric acid (TBA) is treatment B. The acceptance rate of soybean tempe nugget on color, aroma, taste, and texture is in the likes category. Where the most preferred soybean tempe nugget is treatment B with a concentration of broccoli as much as 10%.Keywords : Nugget, Tempe, Broccoli, Oxidation